2019
DOI: 10.1111/aej.12337
|View full text |Cite
|
Sign up to set email alerts
|

When and how do endodontic specialists use cone‐beam computed tomography?

Abstract: This study investigated the use of cone-beam computed tomography (CBCT) by endodontists in Germany and Switzerland. Sixty-eight German endodontic specialists (G-ES), 22 Swiss endodontic specialists (CH-ES) and 95 dentists with a German Master of Science in endodontics (MSc) were invited to participate. Data on the timing of diagnostic assessments, endodontic case difficulty and indications for CBCT use were collected by questionnaire. The frequencies of pre-, intra-and postoperative use of periapical radiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 30 publications
3
26
1
1
Order By: Relevance
“…7 The utilization of CBCT for diagnosing complex endodontic anatomy varies geographically and with the level of qualification of dentists. 8 A survey reported that when missed canals were suspected, dental practitioners ordered CBCT in only 25% of cases. 8 Some studies report that the treatment plan formulated was quite different if preoperative assessment was done with CBCT as compared to when it was done without it, while other studies report insignificant influence.…”
Section: Introductionmentioning
confidence: 99%
“…7 The utilization of CBCT for diagnosing complex endodontic anatomy varies geographically and with the level of qualification of dentists. 8 A survey reported that when missed canals were suspected, dental practitioners ordered CBCT in only 25% of cases. 8 Some studies report that the treatment plan formulated was quite different if preoperative assessment was done with CBCT as compared to when it was done without it, while other studies report insignificant influence.…”
Section: Introductionmentioning
confidence: 99%
“…It is also mentioned that the frequency of CBCT exams depends on the access to tomographic equipment more than any other variables, such as the type of certification of the specialist or the years of experience in the specialty. 14,15 The present study did not cover cases that could be considered of "low complexity" because they do not agree with current consensus and, in general, the evidence does not support the request of a CBCT exam in patients who probably do not require it after analyzing the conventional radiography. 16 However, considering the high contribution of CBCT in this study, it is interesting to wonder what would the effect of CBCT be in those cases where the exam is not usually indicated.…”
Section: Discussionmentioning
confidence: 58%
“…This might not be the reality in other countries, most of them lacking Oral and Maxillofacial Radiologists, where self-referring of CBCT examinations by nonradiologist practitioners who own a machine might be much more prevalent. Self-referral is known to increase the number of radiographic examinations performed, and new data on CBCT in endodontics corroborate this (Levin & Rao 2004, Krug et al 2019. Owing a machine might facilitate its use for economic reasons or simply because it is available, but it is highly uncertain whether this benefits the patient.…”
Section: Discussion Of Resultsmentioning
confidence: 99%